2017
DOI: 10.3390/atmos8080143
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on Rainfall Erosivity in the Huai Luang Watershed, Thailand

Abstract: This study focuses on the impacts of climate change on rainfall erosivity in the Huai Luang watershed, Thailand. The multivariate climate models (IPCC AR5) consisting of CCSM4, CSIRO-MK3.6.0 and MRI-CGCM3 under RCP4.5 and RCP8.5 emission scenarios are analyzed. The Quantile mapping method is used as a downscaling technique to generate future precipitation scenarios which enable the estimation of future rainfall erosivity under possible changes in climatic conditions. The relationship between monthly precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Several issues may arise due to accelerated soil losses on achieving of the Sustainable Development Goals of the United Nations [8], as these goals are dependent on a healthy biophysical environment in which the soil is the base [9]. In order to predict these soil erosion future changes it is necessary precipitation [37,38], monthly [39,40] and daily rainfall indices [41,42]. A different approach estimated projected R changes, using a weather generator with spatial and temporal downscaled precipitation values coming from various GCMs [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several issues may arise due to accelerated soil losses on achieving of the Sustainable Development Goals of the United Nations [8], as these goals are dependent on a healthy biophysical environment in which the soil is the base [9]. In order to predict these soil erosion future changes it is necessary precipitation [37,38], monthly [39,40] and daily rainfall indices [41,42]. A different approach estimated projected R changes, using a weather generator with spatial and temporal downscaled precipitation values coming from various GCMs [43].…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers in Europe examined the potential increase of rainfall erosivity using temporal trends of high resolution precipitation data Water 2020, 12, 687 3 of 20 in Western Germany [34], Belgium [35] and in the Czech Republic [36]. Other studies in various parts of the world used GCMs in conjunction with empirical equations that predict R using annual precipitation [37,38], monthly [39,40] and daily rainfall indices [41,42]. A different approach estimated projected R changes, using a weather generator with spatial and temporal downscaled precipitation values coming from various GCMs [43].Random Forests [44] is a data-driven algorithm in the area of supervised learning which tries to fit a model using a set of paired input variables and their associated output response and can be used in classification and regression problems.…”
mentioning
confidence: 99%
“…Since the statistical characteristics of the raw historical GCM data differ from the reanalysis data, bias correction of GCM outputs is essential. Multiplicative factors, change factors, delta change approach and quantile mapping are a few examples of simple approaches often used to bias correct the raw GCM output and also as downscaling add on [29,[33][34][35][36]. These approaches have some limitations as well, for example, adopting observed distribution and capturing average statistics of historical time series without focusing on the extremes [37][38][39].…”
Section: Bias Correctionmentioning
confidence: 99%
“…The LS factor was computed using parameters such as flow accumulation, cell size and slope. It is observed that, the steeper and longer slope more the risk of higher erosion in many existing studies [33][34][35]. In this study, high resolution (5 m) digital elevation model has been applied to determine the extent area coverage of the hills to make classification based on slope gradients.…”
Section: E Topography (Ls-factor)mentioning
confidence: 99%
“…In this study, eight classes of vegetation covers were identified as Forest, water body, scrub, flower, mixed horticulture, urban settlement, bare land and tea farm. The C values for each vegetation class were excerpted from Tenaga National Berhad Research [34] and the reports of investigations established by previous studies [35,36].…”
Section: F Vegetation Cover (C-factor)mentioning
confidence: 99%